2022
DOI: 10.3390/agronomy12020421
|View full text |Cite
|
Sign up to set email alerts
|

Wood-Ash Fertiliser and Distance from Drainage Ditch Affect the Succession and Biodiversity of Vascular Plant Species in Tree Plantings on Marginal Organic Soil

Abstract: Cutaway peatland is a marginal land, which without further management is an unfavourable environment for plant growth due to low bearing capacity, high acidity and unbalanced nutrient composition of the soil. After wood-ash application, the soil becomes enriched with P and K, creating better conditions for tree growth. In addition to being economically viable, tree plantations ensure long-term carbon storage and promote habitat restoration. In a three-year term, we studied how distance from a drainage ditch an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Considering the mosaic of existing soils in the natural range of this species, the highest abundance was found on limestone soils, with a loamy to clayey texture and the fertility degree as high as possible, such as ABM and FL1. The higher water retention and cation exchange capacity of fine-textured soils could be the reason that justifies it because they increase, respectively, the availability of water and mineral nutrients [ 18 ] and, consequently, plant abundance, growth, and the production of flowers and seeds [ 19 , 20 , 21 ]. The low water-use efficiency of Picris willkommii compared to the other grassland species could justify the preference for fine-textured substrates, with a higher water retention capacity.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Considering the mosaic of existing soils in the natural range of this species, the highest abundance was found on limestone soils, with a loamy to clayey texture and the fertility degree as high as possible, such as ABM and FL1. The higher water retention and cation exchange capacity of fine-textured soils could be the reason that justifies it because they increase, respectively, the availability of water and mineral nutrients [ 18 ] and, consequently, plant abundance, growth, and the production of flowers and seeds [ 19 , 20 , 21 ]. The low water-use efficiency of Picris willkommii compared to the other grassland species could justify the preference for fine-textured substrates, with a higher water retention capacity.…”
Section: Discussionmentioning
confidence: 99%
“…This competition not only affected the emergence of new plants, but also those that had previously emerged, since only 10–25% of the individuals that emerged in early autumn developed and produced seeds. In addition, it demonstrates once again that the next generation does not depend only on the number of seeds generated and the germination potential, but also on other biotic and abiotic factors interacting with each other [ 21 , 23 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to nutrient cycling, biomass production systems on marginal land can also affect plant diversity, according to Zuševica et al [17]. This research group from Latvia found that the establishment of woody crops on organic soils (from former peat extraction) can positively affect plant diversity, whereby the application of ash-based fertilizers and the distances to drainage ditches require special consideration [17]. Furthermore, a better understanding of plant-root bacterial interactions may help to improve the nutrient use efficiency in biomass production on low-yielding (poor) soils.…”
mentioning
confidence: 99%